Pemetaan Potensi Ekonomi Berbasis Budaya Usaha Mikro Kecil Menengah Setu Babakan - Mulyadi; Fatima Tuzzahara Alkaf (FEB-UP Press, 2020)
This activity is carried out with the aim as a form of community service for the Faculty of Economics and Business at the University of Pancasila, while participants participating in this service are expected to be able to achieve (1) Maximize their potential, (2) increase their knowledge and ability in managing their businesses, (3) build confidence to succeed as an SME actor and (4) develop awareness of the potential of tourism villages with cultural diversity and traditional culinary. From the results of the mapping of these activities, the MSMEs Setu Babakan Srengseng Sawah Jagakarsa South Jakarta has the potential to be developed. Because Setu Babakan is a cultural attraction based on Betawi that continues to grow. The products produced by Setu Babakan MSMEs are products based on local culture both culinary (pletok beer, laksa, egg crust, crocodile bread, other Betawi special foods), processing and other services and micro, small and medium enterprises (MSMEs) are mostly businesses which was pioneered from generation to generation. This can be known by the business they started more than 10 or 20 years ago.